Pengaruh Modal Kerja Terhadap Laba Pada PT. Indosat Tbk - Rahman, Erpi; Putri, Cindi Cecilia; Sintia, Kiki (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The purpose of this study was to determine how working capital affects the profit of PT. Indosat Tbk. The population of this quantitative analysis is all consolidated financial data of PT. Indosat Tbk. for 2018-2022. However, the financial condition report of PT. Indosat Tbk. which includes the income statement and balance sheet for the 2018-2022 period is used as a research sample. The documentation approach is a data collection method that utilizes SPSS software to facilitate basic linear regression data analysis.The research findingns indicate that PT. Indosat Tbk’s. profit is positively and marginally affected by working capital. This indivates that modifications to PT. Indosat Tbk’s. woeking capital have little oe no impact on profit.